Restoring semi-arid rangelands on a Greek Aegean island - Hadjigeorgiou I.; Vaitsis T.; Laskaridis G.; Tzanni C. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Sheep farming is an important activity on the Aegean island of Lesvos, where sheep are grazing on the available areas year-round. Since most of the grazed areas are invaded by the xerothermic, undesirable, thorny bush Sarcopoterium spinosum, a rehabilitation trial was designed. Data were collected on the area usage, edapho-climatic conditions and the area vegetation and were used in formulating the rehabilitation strategy targeting a 5-ha area under rainfed conditions. The strategy included: removal of plant cover by mechanical means, soil conditioning (liming and fertilization), reseeding with a mixture of Dactylis glomerata, Medicago sativa and Trifolium subterraneum, and protection from grazing. Grazing was allowed to cattle at the end of the first growth period and to sheep thereafter. Results after fifteen years show that Sarcopoterium spinosum plants are near extinction and an average production of herbaceous vegetation of 2,000 kg dry matter/ha is achieved. It is concluded that rangeland rehabilitation in semi-arid islands presents an interesting option for supporting livestock farming and upgrading the landscape.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)